Perilaku Kreatif Karyawan dalam Mempertahankan Kinerja Pada Masa New Normal Di PTPN X Pabrik Gula Tjoekir - Rindy Dian Ayu Oktavia; Mochammad Isa Anshori (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This research was conducted to find out how the creative behavior of employees in maintaining their performance in the new normal. The research method used in this research is to use qualitative methods using purposive sampling technique or taking informants with certain criteria. In this study, employees who work at PTPN X Tjoekir Sugar Factory are in the human resources division.The data from this study were obtained from direct observation, with in-depth interviews and documentation conducted on 5 selected informants to conduct interviews. Factors that encourage creative behavior of employees in improving their performance vary from one employee to another. There are two factors that encourage employees to perform creative behavior at work. Internal factors are factors that grow from within the individual, while external factors are factors that grow due to encouragement from the environment where the individual lives. Statements obtained from informants are mostly influenced by internal factors, the desire to get promoted, the desire to get more rewards and salaries, but there are also some that are influenced by external factors. So it can be concluded that the influence of internal factors is stronger than external factors because based on the five informants themselves, many of their statements indicate the influence of internal factors, and some of the external influences are encouragement from their own families.